2016
DOI: 10.1515/pjvs-2016-0113
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of pigs diet with zinc and copper as alternative to conventional antimicrobials

Abstract: Modern commercial pig farming systems inflict increased stress in animals, which often leads to various negative changes in the gastro-intestinal tract, especially in the case of piglets. Ban of antibiotics, used as growth promoters, has caused a need for alternatives to conventional antimicrobials in swine diets. Use of pre-/or probiotics, organic acids and plant extracts is often recommended, but it seems that zinc oxide and cooper salts, which were traditionally included in high doses to piglets diet, posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 47 publications
(47 reference statements)
1
52
0
2
Order By: Relevance
“…37 The occurrence of Zn and Cu may have beneficial fertilizing properties, as these are important trace elements for plants, but may also be of environmental concern when present in large quantities, affecting groundwater, surface water, and aquatic animals. [38][39][40][41] We hypothesize that excess levels of Zn and Cu promote transfer of resistance plasmids from ESBL-producing E. coli. The aim of our study was to assess the effect of Zn and Cu on conjugation of bla CMY-2 carrying plasmids from ESBL-producing E. coli collected from retail chicken meat.…”
Section: Introductionmentioning
confidence: 99%
“…37 The occurrence of Zn and Cu may have beneficial fertilizing properties, as these are important trace elements for plants, but may also be of environmental concern when present in large quantities, affecting groundwater, surface water, and aquatic animals. [38][39][40][41] We hypothesize that excess levels of Zn and Cu promote transfer of resistance plasmids from ESBL-producing E. coli. The aim of our study was to assess the effect of Zn and Cu on conjugation of bla CMY-2 carrying plasmids from ESBL-producing E. coli collected from retail chicken meat.…”
Section: Introductionmentioning
confidence: 99%
“…Copper is an indispensable element used in the production of livestock and poultry. Basic copper chloride is an essential additive in feed [16]. Researchers previously found that copper and copper compounds had antiviral effects against dengue virus, in uenza virus, and human immunode ciency virus (HIV) in vitro [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…element used in the production of livestock and poultry. Basic copper chloride is an essential additive in feed [16]. Researchers previously found that copper and copper compounds had antiviral effects against dengue virus, influenza virus, and human immunodeficiency virus (HIV) in vitro [17][18][19].…”
mentioning
confidence: 99%